2000
DOI: 10.1177/026119290002800305
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxicity of Four Different Buffers for Use in Peritoneal Dialysis

Abstract: Various buffers can be used in fluids for peritoneal dialysis (PD). Lactate is the most frequently used buffer, but bicarbonate and pyruvate have been suggested as more bio-compatible alternatives. In the past, acetate was used as a buffer in PD fluids, but was abandoned after being linked with sclerosing peritonitis and loss of ultrafiltration. When a new buffer for PD fluids is introduced, one of its most important characteristics is that it must be non-toxic, i.e. that it does not influence fundamental cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Furthermore, a large multi-center study has shown that the specific method or cell type is of minor importance (14). At our laboratory, we have chosen to use inhibition of cell growth of an in vitro cultured mouse fibroblast cell line (L-929) as the endpoint for cytotoxicity (15). This method represents an internationally well-proven, well-characterized, and reproducible in vitro system, often used as first-line screening for basal cytotoxicity properties.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, a large multi-center study has shown that the specific method or cell type is of minor importance (14). At our laboratory, we have chosen to use inhibition of cell growth of an in vitro cultured mouse fibroblast cell line (L-929) as the endpoint for cytotoxicity (15). This method represents an internationally well-proven, well-characterized, and reproducible in vitro system, often used as first-line screening for basal cytotoxicity properties.…”
Section: Methodsmentioning
confidence: 99%